Fatty acids in cancer: Metabolic functions and potential treatment. Issue 1 (10th March 2023) - Du, Ao; Wang, Zhen; Huang, Tengda; Xue, Shuai; Jiang, Chuang; Qiu, Guoteng; Yuan, Kefei
Abstract: Lipid metabolic reprogramming is one of the important metabolic characteristics of cancer cells. As major components of lipids, fatty acids provide energy and material basis for cancer cell survival. Abnormal fatty acid metabolism has been found in many cancers. Fatty acid uptake, transport, and synthesis are closely related to the pathogenesis of cancer. Meanwhile, fatty acid changes in the membrane structure of cancer cells and signal transduction mediated by signaling lipids are also helping cancer cells survive in the changing microenvironment. Some of these enzymes and metabolites involved in fatty acid metabolism are emerging as unique cancer biomarkers. Multiple studies have shown that disordered fatty acids can regulate tumor cell proliferation, metastasis, and drug resistance. Therefore, targeting fatty acid metabolism has become a promising treatment strategy. Here, we mainly present metabolic alterations of fatty acids, the basic components of lipids, in cancer. We discuss the cancer treatment based on fatty acid and fatty acid metabolism. These may provide a basis for a better understanding of lipid metabolic reprogramming in cancer, and also provide new ideas for cancer biomarker search, drug development, and combination therapy. Abstract : Fatty acids in cancer cells are derived from cellular synthesis and extracellular uptake. Fatty acids are extensively reprogrammed in cancer cells and regulate life activities, including supporting cell growth as energy, influencing cell movement as components of membrane structure, and regulating signal transduction as signaling molecules. Focusing on the role of fatty acids in tumor cells is helpful to find new strategies for tumor treatment.